1990
DOI: 10.1007/bf02126298
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary neuropsychological test results

Abstract: A series of information processing tasks was administered to 22 PKU children aged 8.5 years who had been under dietary treatment since birth as well as to 20 controls of the same age. This contribution presents the results of two tasks from this series: a continuous performance task and a calculation task. The continuous performance task revealed a sustained attention deficit in the PKU group. In the calculation task the PKU children were slower than the controls and this difference increased with task difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 12 publications
1
24
1
Order By: Relevance
“…As this difference was independent of the stimulus interval manipulation it could not be inter preted in terms of an inability to preset a response. Although these findings may seem inconsistent with the results of earlier studies which showed that PKU pa tients perform more slowly and/or less accurately than controls in a variety of information processing tasks [ [29] demonstrated that differences in task performance between PKU patients and controls could be attributed solely to a group of pa tients with Phe levels > 600 |Ltmol/i whereas the perfor mance of patients with Phe-levels < 600 jLimol/1 actually matched that of the controls. Our sample of PKU patients had been continuously maintained on a well-controlled Phe-restricted diet, resulting in average Phe levels that were low compared to the levels generally mentioned in the literature [1,3,5,6,7,14].…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations
“…As this difference was independent of the stimulus interval manipulation it could not be inter preted in terms of an inability to preset a response. Although these findings may seem inconsistent with the results of earlier studies which showed that PKU pa tients perform more slowly and/or less accurately than controls in a variety of information processing tasks [ [29] demonstrated that differences in task performance between PKU patients and controls could be attributed solely to a group of pa tients with Phe levels > 600 |Ltmol/i whereas the perfor mance of patients with Phe-levels < 600 jLimol/1 actually matched that of the controls. Our sample of PKU patients had been continuously maintained on a well-controlled Phe-restricted diet, resulting in average Phe levels that were low compared to the levels generally mentioned in the literature [1,3,5,6,7,14].…”
Section: Discussioncontrasting
confidence: 91%
“…Our sample of PKU patients had been continuously maintained on a well-controlled Phe-restricted diet, resulting in average Phe levels that were low compared to the levels generally mentioned in the literature [1,3,5,6,7,14]. Although the number of patients in our sample with Phe levels > 600 (.Lmol/1 was too small to permit a comparison between patients with "good" and patients with "poor" control (as was done by de Sonneville et al [29]), it seems reasonable to assume that the low Phe levels found in our patient group have in deed contributed to the absence of group differences in the present study. These low Phe levels in combination with the small range of the Phe levels, may also have pre vented strong correlations between biochemical data and performance measures.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…A primary reason for selecting this battery was that it is sensitive to changes in phe concentrations in children (de Sonneville et al 1990;Schmidt et al 1992), and in adults (Pietz et al 1993). It has been demonstrated in PKU patients that a higher phe concentration parallels a slower performance in the sustained attention and divided attention tasks (de Sonneville et al 1990;Schmidt et al 1992).…”
Section: Discussionmentioning
confidence: 97%